2020
DOI: 10.3390/polym12112610
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Study on Color Shift of Injection-Molded Mobile LGP Depending on Surface Micropattern

Abstract: In the display industry, the LCD backlight unit (BLU) module is variously used in mobile phones, notebook computers, monitors, and TVs. The light guide plate (LGP), which is one of the core parts of a BLU, is getting bigger and thinner consistently. Conventional injection methods and injection processes like injection compression molding (ICM) are becoming more complex and harsher with high-speed injection at high mold and melt temperatures. These approaches lead to a change in physical properties and a decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Moreover, the optimal process parameters obtained from the design of experiments improved the fringe pattern and eliminated the local variation of birefringence. In 2020, Kim et al [26] found that conventional injection methods and injection processes like injection compression molding (ICM) are becoming more complex and harsher with high-speed injection at high mold and melt temperatures, with these approaches leading to a change in physical properties. In 2020, Ren et al [27], introducing optical injection, found that, under proper optical injection parameters, two sub-combs originating from two orthogonal polarization components of the VCSEL(vertical-cavity surface-emitting laser) can splice into a broadband total-OFC(optical frequency comb).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Moreover, the optimal process parameters obtained from the design of experiments improved the fringe pattern and eliminated the local variation of birefringence. In 2020, Kim et al [26] found that conventional injection methods and injection processes like injection compression molding (ICM) are becoming more complex and harsher with high-speed injection at high mold and melt temperatures, with these approaches leading to a change in physical properties. In 2020, Ren et al [27], introducing optical injection, found that, under proper optical injection parameters, two sub-combs originating from two orthogonal polarization components of the VCSEL(vertical-cavity surface-emitting laser) can splice into a broadband total-OFC(optical frequency comb).…”
Section: Literature Reviewmentioning
confidence: 99%